2019
DOI: 10.1175/jas-d-19-0128.1
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Observations of Tropical Cyclone Boundary Layer Turbulence over the South China Sea

Abstract: There have been no high-frequency aircraft observations of tropical cyclone (TC) eyewall boundary layer turbulence since two flights into Atlantic hurricanes in the 1980s. We present an analysis of the first TC boundary layer flight observations in the South China Sea by the Hong Kong Observatory comprising four eyewall penetrations. We derive the vertical flux of momentum and vertical momentum diffusivity from observed turbulence parameters. We observe negative (upward) vertical fluxes of tangential momentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This result stresses the importance of the boundary layer in the intensification (especially the RI) of TCs, which has also been shown in previous studies [28,29]. Actually, to better understand the TC structure in the boundary layer, flight observations aimed at the TC boundary layer were conducted in the South China Sea since 2009, which comprised four eyewall penetrations [30]. To better use these observations to improve the RI forecast of a TC, some questions should be first addressed: (i) Does the uncertainty in the boundary layer influence the RI forecast uncertainty of a TC?…”
Section: Introductionsupporting
confidence: 79%
“…This result stresses the importance of the boundary layer in the intensification (especially the RI) of TCs, which has also been shown in previous studies [28,29]. Actually, to better understand the TC structure in the boundary layer, flight observations aimed at the TC boundary layer were conducted in the South China Sea since 2009, which comprised four eyewall penetrations [30]. To better use these observations to improve the RI forecast of a TC, some questions should be first addressed: (i) Does the uncertainty in the boundary layer influence the RI forecast uncertainty of a TC?…”
Section: Introductionsupporting
confidence: 79%
“…The momentum budget estimates of Bell et al (2012) provide C D out to very high winds (10-m wind speeds above 70 m s 21 ), but the large inherent uncertainty in these approximations precludes any definitive conclusion about even the slope of C D versus wind speed beyond 40 m s 21 , let alone its precise value. The direct aircraft measurements of Sparks et al (2019) and Zhao et al (2020) made in Pacific typhoons suggest that the momentum flux changes with wind speed in a way consistent with a saturation of C D ; however, while extending out to 60 m s 21 , the measurements are again quite uncertain. Likewise, other direct measurements of boundary layer turbulence in tropical cyclones, namely, those of Zhang et al (2011a), are also uncertain and scarce in sample size.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, Chen and Li offered an investigation relevant to latent heat flux exchanges at the air-sea interface, which play important roles in the formation and development of tropical cyclones over the ocean [11]. Sparks and Hon presented an analysis of the first boundary layer flight observations on the ocean by the Hong Kong Observatory comprising four eyewall penetrations, which derived the vertical flux of momentum and vertical momentum diffusivity from observed turbulence parameters [12]. Based on generalizations of numerous measurements and calculations, Lukin found that the outer scale of turbulence in the surface layer of the atmosphere depends not only on the height above the underlying surface but also on the type of atmospheric stratification [13].…”
Section: Introductionmentioning
confidence: 99%